2019
DOI: 10.1080/15685551.2019.1699727
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of pH-responsive poly(2-(tert-butylamino)ethyl methacrylate) brushes grafted on mesoporous silica nanoparticles

Abstract: (2019) Surface modification of pH-responsive poly(2-(tert-butylamino)ethyl methacrylate) brushes grafted on mesoporous silica nanoparticles,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
4
13
0
Order By: Relevance
“…5 nm. No significant differences in SEM and TEM images were observed between nonmodified and modified MSNs, which is similar to the observation reported previously [42] ( Figures 1S and 2S). Furthermore, the particle size distribution was investigated using dynamic light scattering (DLS).…”
Section: Resultssupporting
confidence: 91%
“…5 nm. No significant differences in SEM and TEM images were observed between nonmodified and modified MSNs, which is similar to the observation reported previously [42] ( Figures 1S and 2S). Furthermore, the particle size distribution was investigated using dynamic light scattering (DLS).…”
Section: Resultssupporting
confidence: 91%
“…Then, 0.25 mL (2.02 mmol) of 2-bromo-2-methylpropionyl bromide was mixed with 5 mL of DCM, added dropwise into the suspension, and allowed to react for 48 h at room temperature. The HMSN-Br nanoparticles were collected by centrifugation and washed with DCM and ethanol [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, 0.25 mL (2.02 mmol) of 2-bromo-2-methylpropionyl bromide was mixed with 5 mL of DCM, added dropwise into the suspension, and allowed to react for 48 h at room temperature. The HMSN-Br nanoparticles were collected by centrifugation and washed with DCM and ethanol [38] In a typical reaction, 0.4 g of HMSN-Br, 12 mL of ethanol, and 3 mL of water were mixed and degassed with N 2 for 30 min under stirring. 2-Diethylaminoethyl methacrylate (2 mL), 0.0009 g of CuBr 2 , and 0.0067 g of BIPY were added to the mixture.…”
Section: Immobilization Of Bibb Initiator On Hmsns (Hmsn-br)mentioning
confidence: 99%
“…Despite the potential advantages of MSNs for drug delivery applications, pure MSNs tend to aggregate when directly exposed to biological environments, leading to uncontrolled drug release patterns [ 19 , 20 ]. These drawbacks could be minimized by using biocompatible polymers to coat the surface of silica nanoparticles in order to form different structures such as yolk–shell [ 21 ], core–shell [ 22 ], and brushes [ 23 ]. The combination of such polymers and silica nanoparticles not only addresses the aforementioned limitations but can also endow these particles with encapsulated guest molecules and subsequently release them at a later stage in an optimal way [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alswieleh et al successfully incorporated poly(2-(tert-butylamino)ethyl methacrylate) brushes into mesoporous silica nanoparticles via surface-initiated atom transfer radical polymerization (SI-ATRP). The results showed that the polymer brushes were highly swollen when they became protonated at a low pH value and collapsed when deprotonated at pH above 7.5 [ 23 ]. Beagan et al modified the surface of hollow mesoporous silica nanoparticles with glucosamine-poly(2-(diethylamino) ethyl methacrylate) brushes.…”
Section: Introductionmentioning
confidence: 99%